2011
DOI: 10.1111/j.1365-2559.2011.04067.x
|View full text |Cite
|
Sign up to set email alerts
|

Classical lobular breast carcinoma consistently lacks topoisomerase‐IIα gene amplification: implications for the tailored use of anthracycline‐based chemotherapies

Abstract: In the era of personalized and tailored therapies, we suggest that patients affected by the classical lobular subtype of breast carcinoma constantly lack the ad hoc predictive rationale for receiving common chemotherapy that includes anthracyclines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The same was reported in a different study from our group, analyzing DTC-status 3 years after diagnosis [12]. In this previous study it was also observed that DTC-positivity was positively associated with lobular carcinoma, which can be explained by a relative resistance also to the anthracycline-containing chemotherapy [25,30]. Our study supports the selection of higher stage patients into future DTC intervention trials (Table 1), in order to select those with both the traditionally highest risk of relapse and the highest frequency of DTC-positivity.…”
Section: Discussionsupporting
confidence: 79%
“…The same was reported in a different study from our group, analyzing DTC-status 3 years after diagnosis [12]. In this previous study it was also observed that DTC-positivity was positively associated with lobular carcinoma, which can be explained by a relative resistance also to the anthracycline-containing chemotherapy [25,30]. Our study supports the selection of higher stage patients into future DTC intervention trials (Table 1), in order to select those with both the traditionally highest risk of relapse and the highest frequency of DTC-positivity.…”
Section: Discussionsupporting
confidence: 79%
“…Invasive lobular carcinoma patients may potentially benefit less from chemotherapy based on the high‐rate of ER positivity, low mitotic index, and other biomarkers . There is reason to speculate, however, that ILC patients might strongly benefit from adjuvant endocrine therapy since the overwhelming majority of ILC tumors express ER.…”
Section: What Is the Optimal Methods Of Evaluation For Disease Extent mentioning
confidence: 99%
“…• Inverse correlation with tumor grade Brunello et al), suggesting the rationale for the anthracyclines chemotherapy resistance. Indeed, TOPO2A gene amplification was shown to be a good predictor of response to anthracyclines (35).…”
Section: Cicline D1mentioning
confidence: 99%